Mechanisms of financing the fiscal deficit in Iraq - legal study - DikhiL, Ahmed khelef housine (Finance and Business Economies Review, 2022)
comThis research sheds light on the mechanisms adopted by the Iraqi government to finance the financial deficit it suffers from as a result of the irrational fiscal policy, and the significant effects that it entails, especially in the draft general budget law in the way it reached the House of Representatives, especially after the Iraqi government fell between two options. The first is the adoption of a severe austerity policy, while the second is to take a negative stance and go about things as agreed until a new government is elected and bears the burden of searching for a solution to the crisis, in addition to the challenges surrounding the adoption of alternative mechanisms, which makes it more difficult despite being better than the options presented. Not to mention the strange way to solve the crisis by adopting means to finance the deficit without looking for ways to reduce that deficit by reducing public expenditures